Hidravlični turbinski stroji 1 - Biluš, Ignacijo (2020)
Hydraulic Turbomachinery 1. In present publication an attempt has been made to present the hydraulic turbomachinery concisely. The introduction gives a classification of turbomachines. Afterwards, the fundamental physical phenomena that take place in the hydraulic turbomachines are described with the basic equations that relate the transport phenomena in the rotating machines to the basic knowledge of fluid mechanics. This is followed by a chapter on similarity theory and chapters in which the radial and axial machines and their operating characteristics are discussed at the integral level. A separate chapter is devoted to the occurrence of cavitation in hydraulic systems in the theoretical and applied fields. The last chapter in the publication deals with wind turbines, which have gained in importance due to the popularization of renewable energy sources and clearly fall within the scope of the textbook.
Keywords: turbine; pump; axial turbo machine; radial turbo machine; cavitation